Community Interpreting–oriented Terminology Management Tools. - Antón, María Teresa Ortego (International Journal of Language, Translation and Intercultural Communication, 2016)
Unlike translators, who have a great variety of computer-assisted tools for terminology management, interpreters have not benefited from the same level of innovation. In fact, the task of community interpreter is to allow people who do not speak the official language(s) of the country to communicate with the providers of public services so as to facilitate full and equal access to legal, health, education, government and social services. Thus, having taken into account the special needs of community interpreters, in this paper we establish a set of parameters from the conclusions drawn from the literature review to assess to what extent terminology management tools meet these needs. Then, a selection of terminology management tools are analysed. From the results, conclusions are drawn which might suggest a need to take into account new proposals in order to implement terminology management in computer-assisted tools from the view of community interpreting as well as to inform new searching procedures used by trainees and community interpreters.